2011
DOI: 10.1002/ana.22554
|View full text |Cite
|
Sign up to set email alerts
|

Early factors associated with axonal loss after optic neuritis

Abstract: The association of RNFL loss with a prolonged visual evoked potential (VEP) latency suggests that acute and persistent demyelination is associated with increased vulnerability of axons. VEP latency and visual function tests that capture optic nerve function, such as color and contrast, may help identify subjects with a higher risk for axonal loss who are thus more suitable for experimental neuroprotection trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…Our findings were consistent with previous studies that reported significant RNFL thinning within the first 6 months after the acute optic neuritis and that no further significant interval changes were detected from 6 to 24 months. 7,13 As all of our subjects did not present with papillitis, the amount of longitudinal RNFL thinning may not be as dramatic as other study populations 14,15 that included subjects with initial papillitis, since papillitis would give rise to an initial paradoxical increase in RNFL thickness.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our findings were consistent with previous studies that reported significant RNFL thinning within the first 6 months after the acute optic neuritis and that no further significant interval changes were detected from 6 to 24 months. 7,13 As all of our subjects did not present with papillitis, the amount of longitudinal RNFL thinning may not be as dramatic as other study populations 14,15 that included subjects with initial papillitis, since papillitis would give rise to an initial paradoxical increase in RNFL thickness.…”
Section: Discussionmentioning
confidence: 96%
“…First, this allows for the concomitant use of potential neuroprotective drugs in future clinical trials without fear that the effects of systemic steroid use would confound the degree of RNFL thinning. Secondly, the treatment effects of neuroprotective medication can be monitored with OCT, as previously proposed by Henderson et al 7,17 This study had its limitations. Firstly, the assignment of treatment and non-treatment groups was not randomised, but the authors felt that it would be unethical to withhold treatment in those with a high visual demand when systemic steroids can hasten the visual recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the measures did not correlate in this cohort emphasizes that each test addresses distinct components of vision. P100 prolongation early after ON predicts later retinal axonal loss (27), thus VEPs may have utility as a prognostic biomarker. However, an isolated change in VEP latency among stable MS patients may be dissociated from other aspects of visual function and the patient's ability to function.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed by which axonal loss caused by MS disease could lead to tissue degeneration and ultrastructural changes of the retinal ganglionar cells, astrocytes, and endothelial cells [19,20], and are supported by evidence based on the effects of ON on the RNFL [4,21,22,23]. …”
Section: Introductionmentioning
confidence: 94%